Flexible education - Massive Open Online Courses (MOOC) - UMP, PNC (2019)
The ASEM MOOC Stakeholders’ Forum 2019 successfully gathered the expertise from the ASEM MOOC network focusing on the content development of Massive Open Online Courses (MOOC) involving universities and ASEM strategic partners in the region.